Kontribusi Gaya Kepemimpinan, Motivasi Kerja, Iklim Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai di Lingkungan Biro AKPK Undiksha. Tesis. Administrasi Pendidikan, Program Pascasarjana Universitas Pendidikan Ganesha. - Natarini, Luh Rini; Dantes, Kadek Rihendra; Sulindawati, Ni Luh Gede Erni (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to 1) analyze the contribution of leadership style to employee performance in the AKPK Undiksha environment, 2) analyze the contribution of work motivation to employee performance in the AKPK Undiksha environment, 3) analyze the contribution of the work climate to employee performance in the AKPK Undiksha environment, 4) analyze the contribution job satisfaction on employee performance in Undiksha AKPK environment, 5) analyze the contribution of leadership style, work motivation, work climate and job satisfaction to employee performance in Undiksha AKPK environment simultaneously. This research is an ex post-facto research. The population which is also the sample in this study are all employees in the Undiksha AKPK environment, totaling 40 employees. The independent variables in this study are leadership style, work motivation, work climate and job satisfaction, while the dependent variable is employee performance. The data collection method used in this study was a questionnaire. Data analysis used in this study is multiple regression and partial correlation. Based on the research that has been done, it is concluded that: 1) there is a significant contribution of leadership style to employee performance in the Undiksha AKPK environment, 2) there is a significant contribution of work motivation to employee performance in the Undiksha AKPK environment, 3) there is a significant contribution to the work climate employee performance in Undiksha AKPK environment, 4) there is a significant contribution of job satisfaction to employee performance in Undiksha AKPK environment, and 5) there is a simultaneous significant contribution of leadership style, work motivation, work climate and job satisfaction to employee performance in Undiksha AKPK environment.